Taste Profiling Of Centella Asiatica By A Taste Sensor. - A. K. M., Shafrqul Islam; Ismail, Zhari; Ahmad, Mohd Noor; Othman, Abdul Rahman; Dharmaraj, Saravanan; Mohd Shakaff, Ali Yeon (2003)

(untitled)
The usage of herbal products is currently on the rise because of their vast therapeutis potential.